A Comparison of Medial and Lateral Ligament Balance in Functional Versus Simulated Mechanical Alignment in Total Knee Arthroplasty Across CPAK Phenotypes: A Single-Center Study - Anne Ruth van Meijeren; Daniëlle Langeloo; Hans-Peter van Jonbergen; Martin Stevens; Marrigje Floor Meijer (Journal of Clinical Medicine, 2026)
Background/Objectives: Despite the excellent long-term outcomes of total knee arthroplasty (TKA), up to 10% of patients remain dissatisfied. Robotic-assisted TKA enables individualized alignment strategies, such as functional alignment (FA). Proper alignment and soft tissue balance are considered key factors for positive clinical outcomes. This study compared medial and lateral ligament balance between simulated mechanical alignment (MA) and FA across different Coronal Plane Alignment of the Knee (CPAK) types using intraoperative robotic simulations. Methods: In this observational cohort study, 200 patients undergoing primary robotic-assisted TKA were included. Knee laxity was assessed intraoperatively under simulated MA and FA within the same knee. Laxity was defined as medial and lateral joint space opening under varus and valgus stress in flexion and extension. Balance was defined as an absolute difference of ≤2 mm. Outcomes were stratified by native CPAK phenotype in an exploratory subgroup analysis. Results: Functional alignment resulted in significantly improved ligament balance compared to simulated MA across CPAK types. The largest improvements were observed in CPAK type II, with the proportion of overall balanced knees increasing from 7.7% in simulated MA to 88.5% in FA. Improvements were observed in CPAK types II, V, VI and VIII and were mainly driven by a reduction in extension imbalance. Conclusions: Functional alignment leads to improved medial and lateral ligament balance compared to simulated MA. These findings suggest that the effect of the alignment strategy on soft tissue balance may differ according to the underlying knee phenotype.